Formulation and In vitro Evaluation of Oral Floating Tablets of Salbutamol Sulphate: Comparison with Effervescent Tablets (Dhaka University Journal of Pharmaceutical Sciences, 2017)
The aim of this research was to develop and evaluate gastric floating tablets of salbutamol sulphate. The oral delivery of anti-asthmatic salbutamol sulphate tablets were facilitated by preparing floating dosage form which could increase its absorption in the stomach by increasing the gastric residence time of the drug. Floating tablets were formulated by using different polymers like carbopol, xanthan gum, HPMC-K4 MCR and HPMC- K100 MCR with different proportions. A comparative study of normal effervescent tablets of salbutamol sulphate had also been done. The prepared tablets were evaluated for all their physicochemical properties and in vitro buoyancy study. In vitro dissolution studies of the formulations were done in pH 6.8 phosphate buffer using USP apparatus 2 (paddle method) at 50 rpm. Percent drug release of the formulations (F-1 to F-11) was from 87.34%- 99.12% after 12 hours. From the results, F-11 was selected as an optimized formulation based on 12 h drug release which showed minimal floating lag time and maximum floating time. On the other hand, 100% drug was released within 2 hours from the F-12 of effervescent salbutamol sulphate tablets in which polymer was absent while gas generating sodium bicarbonate and citric acid were present. The results of the study were consistent and may encourage formulating similar dosage form with other drugs.Dhaka Univ. J. Pharm. Sci. 15(2): 203-208, 2016 (December)